CODE MIXING AND CODE SWITCHING IN MAUDY AYUNDA’S VIDEO YOUTUBE CHANNEL - Riska Rosana; Fitri Palupi Kusumawati; Amirudin Latif; Eva Faliyanti (Journal of English Education and Entrepreneurship (JEEP), 2025)
The aim of this research is to find out the types and functions of code- mixing and code-switching in Maudy Ayunda Video. Descriptive qualitative is the method of this research. The source of this research is Maudy Ayunda video YouTube channel with the title how to communicate effectively in the workplace and how I manage stress. The object of this research is Maudy Ayunda's speaking in the video YouTube Channel. The instruments in this research are researcher, documentation and tabulation. The result of this research found three types of code mixing such as 66 insertion, 9 alternation and 1 congruent lexicalization. The types of code switching comprise two types, they are: 12 Inter sentential switching , 28 Intra sentential switching. The functios of code mixing comprise six functions such as 1 Quotation, 2 Addressee specification, 4 Interjection, 43 Message qualification, 12 Personalization and objectivization, and 40 Facility expression. The functios of code switching comprise six functions such as 2 Quotation, 1 Addressee specification, 1 Interjection, 27 Message qualification, 8 Personalization and objectivization, and 13 Facility expression. Based on the results of the research, it can be concluded that the results of this study are the existence of code mixing and code switching of Indonesian with English utterance on Maudy Ayunda video Youtube channel.